Asymmetric Cascade Catalysis with Chiral Polyoxometalate‐Based Frameworks: Sequential Direct Aldol and Epoxidation Reactions. Issue 10 (3rd May 2017) - Han, Qiuxia; Li, Wenwen; Wang, Shugai; He, Jiachen; Du, Wei; Li, Mingxue
Abstract: Catalytic asymmetric cascade reactions in which the substrates are transferred through well‐choreographed consecutive independent steps by a single catalyst have received increasing interest. By incorporating a chiral organocatalyst pyrrolidine, an oxidation catalyst polyoxometalate and a Lewis acid catalyst copper(II) into a single porous coordination network (PCN), two enantiomorph CuW‐PYIs (PYI=pyrrolidine‐2‐yl‐imidazole) with novel Kagomé lattice were achieved and applied in the conversion of aldehyde with ketone into value‐added chiral epoxy ketones in a one‐pot procedure. The chiral pyrrolidine organocatalysts interact with the carbonyl group of ketones throughout the reaction, which is beneficial for achieving compatibility between the reaction intermediates and synergy of the multiple catalytic cycles, thus driving the direct aldol/epoxidation cascade reaction in an orderly and asymmetrical way. Moreover, the "two‐center catalysis" principle was well demonstrated in the direct aldol/epoxidation cascade reactions. Abstract : Three sites working together : Two enantiomorph CuW‐PYIs (PYI=pyrrolidine‐2‐yl‐imidazole) with novel Kagomé lattice are prepared from a chiral organocatalyst, a polyoxometalate oxidation catalyst, and a Lewis acid catalyst. They show satisfactory yields and enantioselectivities in the cascade direct aldol/epoxidation reactions by synergism of the multiple catalytic sites.